2022
DOI: 10.3390/agronomy12061262
|View full text |Cite
|
Sign up to set email alerts
|

Growth Response and Dry Matter Partitioning of Quality Protein Maize (Zea mays L.) Genotypes under Aluminum Toxicity

Abstract: In this work, 75 quality protein maize (QPM) inbred lines were evaluated for aluminum tolerance using a nutrient solution assay in a laboratory and a soil-based technique in a greenhouse tunnel. The experiment was set up in a completely randomized design with three replications in the laboratory, and a randomized complete block design was used in the greenhouse. Aluminum toxicity was generated by amending a nutrient solution with 600 µM of aluminum sulfate (Al2 [SO4]3) in the laboratory, and Al2 [SO4]3 was app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…The experiment was laid out in a randomized complete block design (RCBD) with three replications in three blocks. The experimental procedure was adopted from [ 14 ] where alluvial soils, which were classified as Haplic Cambisol in accordance with the World Reference Base for Soil Resources (WRB) system [ 30 ] (pH 5.8), were collected from the UFH farm. The soil was watered to field capacity and incubated with Al sulphate (Al 2 [SO 4 ] 3 ) for 48 h before planting.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The experiment was laid out in a randomized complete block design (RCBD) with three replications in three blocks. The experimental procedure was adopted from [ 14 ] where alluvial soils, which were classified as Haplic Cambisol in accordance with the World Reference Base for Soil Resources (WRB) system [ 30 ] (pH 5.8), were collected from the UFH farm. The soil was watered to field capacity and incubated with Al sulphate (Al 2 [SO 4 ] 3 ) for 48 h before planting.…”
Section: Methodsmentioning
confidence: 99%
“…Although field testing has proved to be the most effective in testing maize genotypes for Al tolerance, it is very expensive and time-consuming [ 11 , 12 ]. Laboratory- or greenhouse-based testing techniques offer cheap, easy, and quick alternatives to screening large sets of genotypes for Al tolerance [ 13 , 14 ]. The other advantage of laboratory- and greenhouse-based testing methods is that they are very amenable to seedling-stage testing techniques.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It indicates that the maize line has a critical limit to survive under certain stress conditions. Zishiri et al (2022) also reported no hematoxylin stains on the roots of Al-tolerant inbred lines.…”
Section: Estimation Of Al Tolerance Of Maize Lines By Hematoxylin Sta...mentioning
confidence: 99%
“…Root length is an important trait in measuring maize tolerance to Al stress, which is influenced by the action of additive and nonadditive genes (Ndeke and Tembo 2019). Al concentrations for testing the tolerance level of maize genotypes through a nutrient culture based on relative root growth ranged from 6-16 ppm (Giannakoula et al 2010;Zishiri et al 2022).…”
Section: Introductionmentioning
confidence: 99%